2014
DOI: 10.1159/000369012
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of Growth Hormone Therapy in Children with Noonan Syndrome: A Review of the Evidence

Abstract: Noonan syndrome is a genetic disorder associated with short stature. We reviewed 15 studies in which growth hormone (GH) therapy was used in children with Noonan syndrome. Data show consistent increases in mean height standard deviation score (SDS), with first-year changes of up to 1.26 SDS. Among studies reporting adult or near-adult height, GH therapy over 5-7 years resulted in adult height SDS from -0.6 to -2.1, with up to 60% of subjects in some studies achieving adult height within 1 SDS of mid-parental h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 45 publications
0
49
0
Order By: Relevance
“…Previous studies of GH in Noonan syndrome have consistently reported increases in mean height SDS values or mean height velocity using doses of 0.026-0.066 mg/kg/day (reviewed in [11]. An earlier study in Japan in 15 children with Noonan syndrome were treated with a dose of 0.5 IU/kg/week (i.e.…”
Section: Endocrine Journal Advance Publicationmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies of GH in Noonan syndrome have consistently reported increases in mean height SDS values or mean height velocity using doses of 0.026-0.066 mg/kg/day (reviewed in [11]. An earlier study in Japan in 15 children with Noonan syndrome were treated with a dose of 0.5 IU/kg/week (i.e.…”
Section: Endocrine Journal Advance Publicationmentioning
confidence: 99%
“…This study has several strengths: it was double-blind, included a comparison between two dose groups, and the number of patients was relatively large compared to previous studies of the use of GH in Noonan syndrome [11,[16][17][18]. A further strength is the use of reference values for height SDS for Japanese patients with Noonan syndrome, in addition to Japanese national reference data for children, to evaluate the growth promoting effect of GH.…”
Section: Endocrine Journal Advance Publicationmentioning
confidence: 99%
See 2 more Smart Citations
“…Several trials have shown that rhGH increases adult height (AH) SDS, but most trials were of limited size and none had the design of a randomized clinical trial [12, 13]. Despite the limited AH data, rhGH treatment is included in the current guidelines for the management of short patients with NS [14] and was approved in some countries, including the United States, for this indication.…”
Section: Introductionmentioning
confidence: 99%